Evaluation of glutathione S-transferases expression as biomarkers by heavy metals in Geloina expansa from Sepang Besar River, Selangor, Malaysia - Wakid, Sarini Ahmad; Abd Aziz, Nor Azwady Abd; Alias, Zazali; Mustafa, Muskhazli; Syazwan, Wan Mohd; Zulkifli, Syaizwan Zahmir (Universiti Putra Malaysia Press, 2024)
Glutathione S-transferases (GSTs) are enzymes involved in phase II of detoxification metabolism and could be used as biomarkers for water pollution. This study aims to determine heavy metal concentrations in the soft tissue of the mangrove clam Geloina expansa, as well as the expression of GSTs in the species. The acid digestion method was used to digest the samples, followed by a standard USEPA 6010B procedure using inductively coupled plasma optical emission spectrometry (ICP-OES) to measure the heavy metal contents in the samples. GST enzyme activity was measured using 1-chloro-2, 4-dinitrobenzene (CDNB) as substrate. One-way ANOVA was performed to compare the mean values of heavy metal concentration, protein concentration, enzyme activity, and specific activity. There was a significant difference (p<0.05) for Zn, total protein, and specific activity in G. expansa, but no significant difference in Pb, Cu and enzyme activity. GST enzyme activities were estimated at 0.16 ± 0.01 µmol/min, with a protein content of 1.24 ± 0.04 mg. The specific activity for GST was 0.13 ± 0.01 µmol/ min/mg, calculated as the ratio of enzyme activity to the total protein. GST-specific activity positively correlates with Pb concentration in the soft tissue of G. expansa. Detailed studies on the effects of pollution on the expression of GST need to be further investigated for the future use of this species as an efficient biomarker model.